The optical bandgap of lithium niobate (LiNbO3) and its dependence with temperature - Zanatta, A.R. (Results in physics, 2022)
•This work investigates the optical bandgap Egap of congruent LiNbO3, as determined by optical transmission measurements.•Accordingly, the indirect Egap of LiNbO3 was found to comply withEgapINDT=3.96-0.311coth0.042kBT-1, rendering EgapIND300K=3.77±0.05 eV. Notwithstanding the great scientific−technological interest in lithium niobate (LiNbO3), its optical bandgap Egap has been subject of intense discussion. So far, the literature exhibits different Egap values spanning over about 2 eV and comprises a mixture of compositions, structures, and theoretical methods − not always clearly indicated or discussed. In view of that, this work presents a thorough investigation of the Egap (at room-temperature and in the ∼80–800 K temperature range) of the congruent ferroelectric LiNbO3 (Z-cut) single crystal.